2020
DOI: 10.5222/mmj.2020.98512
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variations of Peroneus Tertius: A Cadaveric Study with Anatomical and Clinical Consideration

Abstract: Objective The objective of this study was to highlight variations in the morphology of peroneus tertius muscle owing to its evolutional, academic, and clinical importance. Methods Sixty-six disarticulated lower limbs were used to study the morphological variations of peroneus tertius (PT) muscle like absence, duplication, accessory PT muscle, and abnormal site of origin and insertion. Detailed dissection was performed to study the proximal and distal attachments of PT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similarly, Stevens et al, 1993 reports 87% of studied specimens have an origin extending proximal to the distal third of the fibula [3]. Contradictory findings of some studies show that PT originates mostly from the distal third of the fibula [11,16]. Thus, it could be suggested that the proposed classification be further improved.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Stevens et al, 1993 reports 87% of studied specimens have an origin extending proximal to the distal third of the fibula [3]. Contradictory findings of some studies show that PT originates mostly from the distal third of the fibula [11,16]. Thus, it could be suggested that the proposed classification be further improved.…”
Section: Discussionmentioning
confidence: 91%
“…The PT is further utilized in plastic surgery and orthopedic surgery for tendonoplasty, tendon transfer, or resection procedures on the foot [8]. Earlier studies have noted variations of PT [3,[9][10][11] and a recent study [9] has introduced a classification system for the sites of origin and insertion.…”
Section: Introductionmentioning
confidence: 99%
“…It is used as a local muscle flap for the treatment of osteomyelitis, in the lower limb ( 38 ). Its tendon is preferred in surgical procedures such as resection of the foot, tendoplasty, tendon transfer, and ligament reconstructions particularly ankle joint ( 39 ). A recent study has demonstrated a hypertrophied tendon and/or low-lying muscle belly of PTM causing anterolateral ankle and rearfoot pain ( 40 ).…”
Section: Discussionmentioning
confidence: 99%